Impact of Familiar Medicine Program on adolescent sexuality care in Maisí (Original) (REDEL. Revista Granmense de Desarrollo Local, 2023)
Adolescent sexuality is a vital process influenced by the social context, which is why it requires a collaborative-educational approach between the professional profiles involved in the Familiar Medicine Program, This study has been conducted since 2021. With the application of theoretical, empirical and mathematical-statistical methods, the references and theoretical foundations were determined and its initial state was diagnosed in a sample of adolescents of 9th grade of the Álvaro Reynoso Mixed Center, of the municipality of Maisí. The objective is to develop a health education program on sexuality focused on instruction, training and attitudinal evaluation to improve the relationship educational preparation - responsible sexuality. The results showed better levels of learning with attitudinal transformations towards responsible sexuality in adolescents, samples of effectiveness and relevance of the program developed.
Keywords: Impact; familiar medicine program; sexuality care; adolescents